Does corporate social responsibility encourage sustainable innovation adoption? Empirical evidence from Luxembourg. (27th December 2018) - Poussing, Nicolas
Abstract: This contribution explores how corporate social responsibility (CSR) might influence the adoption of sustainable innovation. Previous research reveals that CSR effects depend on the specific CSR practices considered; this study accordingly investigates different measures of CSR practices with a strategic perspective: strategic versus responsive CSR. The empirical analysis is based on a survey carried out in Luxembourg in 2008, pertaining to CSR practices in firms, combined with the Community Innovation Survey of 2012. The results gathered from a sample of 286 firms, obtained with a Heckman procedure, highlight the importance of differentiating CSR strategies. Specifically, the results show that CSR activities in general do not lead to sustainable innovation adoption, but strategic CSR can have an effect on its adoption.